Studies on Genetic Variability and Heritability in Bulb Onion (Allium cepa L.) in North-Western Plains of India - J S Khosa; A S Dhatt (Journal of Horticultural Sciences, 2013)
A study on genetic variability, heritability and genetic advance was carried out in bulb onion for 13 traits using 43 accessions. The range of variation was highest for bolting (0 to 51.30%), followed by days to maturity (110 to 155 days) and bulb weight (44 to 87.03g). Values for phenotypic coefficient of variation were higher than corresponding genotypic coefficient of variation for all the characters studied. Higher heritability estimates were obtained for plant height, leaf length, days to maturity, number of scales per bulb, polar diameter, equatorial diameter and TSS. Bolting, bulb weight, neck-to-bulb ratio and the lachrymatory factor showed moderate heritability, while, lowest values were observed for leaf girth and number of leaves per plant. Genetic advance varied from 0.06 to 21.82 for leaf girth and bolting, respectively.